Prototipe Knowledge Management System Untuk Membantu Pengurusan Jenjang Jabatan Akademik Dengan Metode SECI Pada STMIK XYZ - Nur Nawaningtyas Pusparini; Agus Budiyantara (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Repose the Law Republic of Indonesia Number 37 of 2009 on Clause 8 states that a lecturer has a workload of at least 12 (twelve) credits and a maximum of 16 (sixteen) credits each semester in accordance with his academic qualifications. At this time STMIK Widuri has carried out a process of sharing knowledge between lecturers to help with academic levels. But in its implementation, problems were found. First, lecturers do not actively report Tri Dharma activities, so the number of lecturers who have academic positions is only 41.6%. This condition is due to the lack of information possessed by lecturers related to the procedures for managing academic levels, the lecturer does not understand what stages must be taken to take care of academic positions. Second, the unavailability of media that facilitates lecturers in terms of sharing knowledge and experience for the management of academic positions so that the process to improve academic levels is hampered and takes longer which means the process for advancing his career requires a longer period of time. This study aims to create a prototype knowledge management system (KMS) with the SECI method and data collection is obtained through interviews, observation and literature study. Software testing uses the User Acceptance Test (UAT). The results of this study produce a web-based KSM prototype with the test results getting a percentage of 76%, which means the system can be accepted and as expected.